The Longitudinal Relationship Between Depression and Walking Behavior in Older Latinos: The "¡Caminemos!" Study. (March 2013) - Hernandez, Rosalba; Prohaska, Thomas R.; Wang, Pin-Chieh; Sarkisian, Catherine A.
Objectives: This study sought to evaluate the relationship between baseline depression and prospective engagement in walking and exercise behavior after enrollment in an exercise intervention.Methods: The study used baseline, 1-month, 12-month, and 24-month in-person interview and pedometer data collected from Latinos aged >60 years participating in an exercise intervention (¡ Caminemos! ) at 27 senior centers ( n = 572).Results: After joining an exercise intervention, and when using continuous pedometer data and scores from the Yale Physical Activity Survey (YPAS) as the outcomes of interest, older adults with baseline depression exhibited comparable levels of physical activity across time when compared to their nondepressed counterparts. Significant difference in physical activity levels between the depressed and nondepressed subgroups no longer existed within one month of initiating the exercise intervention.Discussion: Among sedentary older Latino adults, having depression may not delay exercise initiation nor does it appear to prevent achievement or maintenance of an exercise program.